Protective effects of leaf juice of Brassica rapa on radio-damage of mouse - QIAN Xiao-wei; ZHU Mu-yuan; LIU Chun-lei; NI Xiang-yong; CHEN Xiao-qun (浙江大学学报. 农业与生命科学版)
The protection and repair effects of Brassica rapa leaf juice on radio-damage mouse induced by 60Coγ-rays were studied with the methods of measuring hemogram of mice, classifying of WBC, measuring wieght of the spleens and chest glands, and the micronucleus test. The results show that leaf juice of Brassica rapa irrigated after or before radiation was significantly effective in curing the decreasing of white blood cell, red blood cell and platelet induced by 60Coγ-radiation. The leaf juice of Brassica rapa could also protect normal immune function of spleen and thymus of mice and increase the immunocyte number. The leaf juice of Brassica rapa could apparently reduce micronucleus of PCE induced by 60Coγ-rays in bone narrow of mice. It shows that leaf juice of Brassica rapa can remarkably protect and repair the injury radiated with 60Coγ-rays. So the leaf juice of Brassica rapa has efficient capacity of antiradiation and repair the injury of radiation. The possible mechanism of antiradiation of leaf juice of Brassica rapa was discussed in the paper.